Fasciola spp. in Southeast Asia: A systematic review. - Vinh Hoang Quang; Bruno Levecke; Dung Do Trung; Brecht Devleesschauwer; Binh Vu Thi Lam; Kathy Goossens; Katja Polman; Steven Callens; Pierre Dorny; Veronique Dermauw (Public Library of Science (PLoS), 2024)
Background Fasciolosis is an emerging public health threat in a number of regions worldwide. To date, we lack an overview of both its occurrence and distribution in Southeast Asia across all actors involved in the life cycle, which impedes the development of disease control measures. Therefore, our objective was to collect recent information on the distribution and the prevalence of Fasciola spp. and the associated risk factors for infection in humans, animals, snails and plant carriers in Southeast Asia. Methodology Bibliographic and grey literature databases as well as reference lists of important review articles were searched for relevant records published between January 1st, 2000, and June 30th, 2022. The systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for reporting systematic reviews. A total of 3,887 records were retrieved, of which 100 were included in the final analysis. Principal findings The studies focused mainly on one host species (96.0%), with Fasciola spp. infection in animals being the most studied (72.0%), followed by humans (21.0%). Based on the used inclusion and exclusion criteria, reports were retrieved describing the presence of Fasciola spp. infection in seven out of 11 countries in Southeast Asia. Depending on the diagnostic tool applied, the prevalence of Fasciola spp. infection ranged between 0.3% and 66.7% in humans, between 0% and 97.8% in animals, and between 0% and 66.2% in snails. There were no studies reporting the presence of metacercariae on plant carriers. Conclusions/significance Our study reconfirms that Fasciola spp. infections are widespread and highly prevalent in Southeast Asia, but it remains difficult to accurately assess the true occurrence of Fasciola spp. in absence of well-designed surveys covering all hosts. As next steps we propose to assess the occurrence of the infection across all actors involved in the transmission, to identify associated risk factors and to estimate the burden of the disease to support national and international decision makers.